Determination of Thiophanate-Methyl and Carbendazim from Environmental Water by Liquid-Liquid Microextraction (LLME) Using a Terpenoid-Based Hydrophobic Deep Eutectic Solvent and High-Performance Liquid Chromatography (HPLC). (24th May 2022) - He, Sile; Tang, Weiyang; Row, Kyung Ho
Abstract: A hydrophobic deep eutectic solvent (DES) based vortex-assisted liquid-liquid microextraction (LLME) procedure was developed for the effective and rapid determination of thiophanate-methyl (TM) and carbendazim (CA) in lake water and tap water samples, with an excellence extraction efficiency (recovery: 87.2% to 97.4%, enrichment factor: 87.2 to 97.4). Twelve hydrophobic DESs based on terpenoids and fatty acids/alcohols were prepared, and those with the highest recovery for TM and CA were selected. The main parameters, including assisting methods, molar ratio of DES components, volume of DES, and NaCl content that may affect vortex-assisted LLME, were optimized. The intra-day and inter-day relative standard deviation (RSD) of this method were from 1.7% to 3.8% and 1.8% to 4.1%, showing excellent precision. The proposed method exhibited suitable limits of detection (TM: 0.053 µg/mL; CA: 0.007 µg/mL) and limits of quantification (TM: 0.177 µg/mL; CA: 0.024 µg/mL).